Penerapan Model Pembelajaran Conceptual Understanding Procedures untuk Meningkatkan Kemampuan Literasi Sains Siswa SMP di Kabupaten Tegal (UPEJ Unnes Physics Education Journal, 2017)
Inactivity and less varied learning model of science used by teachers in Tegal Region causes students to understand less about the concept of science lesson. This research aims to determine (1) the difference in the increase of science literacy skills of junior high school students in Tegal District between using the conceptual learning model with the lecture model, (2) the students' literacy ability profile. Experimental design study with pretest-posttest control group design. The sample of this research use the students of class VIII SMP X Slawi, SMP Y Dukuhwaru and MTs Z. Each school is randomly selected two classes, as experiment class and control class. The variables measured are the improvement of science literacy ability, the availability of science as the body of knowledge, science as a way of thinking, science as the process of investigation and interaction of science, technology and society. Wake up is the improvement of literacy ability of science with CUPs better than lecture method. The profile of each school increases as follows: SMP Negeri X Slawi has an added value of 0.12 SMP Negeri Y Dukuhwaru 0.36 and MTs Z 0.07. The high-down science literacy enhancement profile is as follows: Interaction of science, technology and society, science as a body of knowledge, science as a process of investigation, and science as a way of thinking. The results of this study show that the conceptual learning model Conceptual Procedure (CUPs) can effectively improve the science literacy ability of middle school students with medium and high category in Tegal regency. Less effective for low category SMP.